EXPLORING TEACHER EDUCATORS’ UNDERSTANDING OF CRITICAL PEDAGOGY AND ITS IMPLEMENTATION IN THE ENGLISH READING CLASS - Waliyadin Waliyadin; Zaharil Anasy; Desi Nahartini (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTGrounded in the Freire’s (1971) critical pedagogy premise stating that education should impact social change and reading words should be followed by reading the world, this study explores the experiences of English language teachers who teach English reading classes with the critical pedagogy approach. We employed qualitative research with a case study as the research design to dig into the depth of teachers’ perspectives. The data were garnered through in-depth interviews with four lecturers and analyzed following Braun and Clarke’s (2006) thematic analysis. The present study revealed that teachers’ understanding of critical pedagogy is not explicitly stated by defining or explaining the notion of critical pedagogy. However, some stages and components of critical pedagogy can be identified, showing that to a certain degree the teachers implement critical pedagogy in their reading classes.ABSTRAKBerdasarkan premis pedagogi kritis Freire (1971) yang menyatakan bahwa pendidikan harus berdampak pada perubahan sosial dan membaca kata-kata harus diikuti dengan membaca dunia, penelitian ini mengeksplorasi pengalaman guru bahasa Inggris yang mengajar membaca bahasa Inggris dengan pendekatan pedagogi kritis. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus sebagai desain penelitian untuk menggali lebih dalam tentang perspektif guru. Data dikumpulkan melalui wawancara mendalam dengan empat dosen dan dianalisis mengikuti analisis tematik Braun dan Clarke (2006). Penelitian ini mengungkapkan bahwa pemahaman guru tentang pedagogi kritis tidak dinyatakan secara eksplisit dengan mendefinisikan atau menjelaskan pengertian pedagogi kritis. Akan tetapi beberapa tahapan dan komponen pedagogi kritis dapat diidentifikasi yang menunjukkan bahwa guru pada taraf tertentu menerapkan pedagogi kritis di kelas membaca.How to Cite: Waliyadin, Anasy, Z., Nahartini, D. (2023). Exploring Teacher Educators’ Understanding of Critical Pedagogy and its Implementation in the English Reading Class. IJEE (Indonesian Journal of English Education), 10(1), 182-206. doi:10.15408/ijee.v10i1.31894